METHOD AND APPARATUS FOR SPECIFYING CAUSE OF ABNORMALITY OF DEVICE - OKUMURA HIRONOBU (2003)
PROBLEM TO BE SOLVED: To certainly specify causes of occurrences of abnormalities of a variety of devices such as a heating device, a cooling device, a sterilizer, a water- treatment device and a food machine. SOLUTION: A method for specifying cause of abnormality of device monitors an operating state of a device 1 and when the abnormalities occur in the device 1, specifies a cause of occurrences of the abnormalities based on a monitoring result related to the cause of the occurrences of the abnormalities. An apparatus for specifying of abnormality of device comprises a monitoring means of the operating state of the device 1, a means 22 of determining the abnormalities of the device 1 based on the monitoring result from the monitoring means, a means 23 of specifying the causes of occurrences of the abnormalities based on the determining result of the abnormalities and the monitoring result and a notifying means 24 of the causes of the occurrences.